Regionális mintázatok a preszókratikus filozófiában - Molnár, Gábor (Közép-Európai Közlemények, 2012)
The paper investigates the role of geographical factors in the origins and development of early Greek philosophy. It argues, first, that Jan Assmann‟s theory of hypolepsis offers a plausible answer to the Weberian question concerning the origins of „occidental rationalism.‟ Then it set outs to analyze, from a regionalist point of view, the emergence of one of the necessary conditions, identified by Assmann, for hypoleptic intertextuality: social institutions supporting the conversation with long past texts. Two stages in the history of early Greek philosophy are examined: the Milesian period (ca. the first half of the 6th century B. C.) and an –inferred –Ionian one (third quarter of the same century). In the former case the historical possibility of such a supportive social institution is considered (a more or less institutionalized intellectual “school”), whereas in the latter case, the motives for, and the possible forms of, the diffusion of philosophical cultural practice as well as knowledge are investigated.